The Cambridge companion to European criminal law - Ambos, Kai; Rackow, Peter (Cambridge companions to law, 2023)
"The Cambridge Companion to European Criminal Law is of interest for a broad range of readers, from law students and the interested public, to specialized practitioners and legal scholars. Its essays, written by renowned international experts, combine the highest academic standards with comprehensibility"-- Provided by publisher